2012
DOI: 10.1515/1948-4682.1220
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Policy Narratives and the Public Policy Arena: Obesity as a Lesson in Public Policy Development

Abstract: As witnessed by recent national policy battles over health care and climate change, the policy environment in the United States (U.S.) is increasingly politically polarized. U.S. public policy is progressively driven by divisive symbols and dominated by morality debates often articulated in the form of emotional narratives. One such issue that has gained attention in the U.S., partially due to efforts of First Lady Michelle Obama, is the increasing levels of obesity. Obesity policy advocates warn that the U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Thirdly, thematic evolution analysis demonstrates a shift in emphasis from "health care policy" and "policy analysis" to "human" and "policy making." While this reflects the field's adaptation to shifting contexts and priorities, it is essential to question whether NPF research captures the evolving nuances and complexities of health policy and to what extent this focus reflects contemporary realities (Clemons et al, 2012;Cullerton et al, 2022;Derkyi-Kwarteng et al, 2021;Wallace et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, thematic evolution analysis demonstrates a shift in emphasis from "health care policy" and "policy analysis" to "human" and "policy making." While this reflects the field's adaptation to shifting contexts and priorities, it is essential to question whether NPF research captures the evolving nuances and complexities of health policy and to what extent this focus reflects contemporary realities (Clemons et al, 2012;Cullerton et al, 2022;Derkyi-Kwarteng et al, 2021;Wallace et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We have recommended support for PHTs to help them articulate clear narratives regarding the potential links between availability and harms; it would be valuable to evaluate the process and outcomes of disseminating such narratives and their impact on decision-making. 44,137 Future studies evaluating changes in availability could benefit from considering the mechanisms of change suggested by our interviewees and including relevant outcomes to add to understanding of the diverse impacts of alcohol outlets on alcohol-related harms in the long and short term.…”
Section: Mechanisms Of Impact Of Availability On Harmsmentioning
confidence: 99%
“…(2018, 183) found that “congruent narratives intensify an individual's policy stances and beliefs. As perception of congruence increases, an individual is more likely to be persuaded by the narrative.” Several NPF studies (Clemons, McBeth and Kusko 2012; Husmann 2015; Lybecker, McBeth and Kusko 2013; McBeth, Lybecker and Garner 2010) demonstrate that individuals accept narratives congruent with their prior cultural beliefs. Thus, it is likely individuals identify with those narrators who pose these narratives.…”
Section: Literature Reviewmentioning
confidence: 99%